Does computer proficiency and work motivation influence career development in teacher professional education? - Parsa, I Made; Bani, Marsi (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the influence of computer skills and work motivation on the career development of teacher candidates enrolled in the Teacher Professional Education In-Service Program (Batch 1 of 2023) at the Institute for Educational Personnel Development, Nusa Cendana University, Kupang. Employing a quantitative approach with an ex-post facto design, data were collected from a randomly selected sample and analyzed using Path Analysis. The findings reveal that computer skills have a significant positive effect on work motivation (path coefficient = 0.646; ρ < 0.001), and work motivation has a direct impact on teacher career outcomes (path coefficient = 0.346; ρ = 0.030). Additionally, computer skills indirectly influence teacher careers through work motivation (combined path coefficient = 0.233). The model accounts for 97.8% of the variance in teacher career development (R² = 0.978). These results underscore the need for teacher education programs to incorporate comprehensive digital literacy training and motivational strategies. Enhancing infrastructure and equitable access to technology is also vital to support professional growth. Future studies should examine long-term impacts to inform policy and practice in teacher professional development.